Employing indicators for prioritization of fish assemblage with a view to manage freshwater fish diversity and ecosystem health in the tributaries of Ganges basin, India. Issue 1 (3rd April 2017) - Sarkar, U. K.; Dubey, V. K.; Singh, S. P.; Singh, Atul K.
Abstract : The major tributaries of the river Ganges basin are currently threatened by various anthropogenic activities which are hampering the ecosystem stability and fish biodiversity of the basin. Multiple indicators were used to prioritize the fish assemblages in the tributaries and to develop an index that is responsive to human-induced environmental changes. A high percentage of invasive species was described with the orgin index at the most disturbed sites of rivers Gomti and Betwa which also represented a substantial amount of biological disturbance. The Fisheries Assessment Integrity Index based on ecological integrity of different segments of the rivers was used to prioritize different sampling sites of the tributaries. Some of the sampling sites in Gomti and Betwa rivers are reflecting disturbed fish assemblages, a very low Fisheries Assessment Integrity Index score, few threatened species, and a high proportion of invasive species. Principal components analysis of the sampling sites, along with fish assemblage, reflected the influence of the habitat parameters on structuring the assemblage pattern. This study identified depth, flow, water quality and land uses in shaping fish assemblages. The combination of various indices in this study should provide more accurate measures in identifying sites of high conservation value.